Penyebaran Informasi Program “Children Special Protection” (CSP) dan Pengaruhnya terhadap Perilaku Anak Jalanan - Jeanny Maria Fatimah (MediaTor (Jurnal Komunikasi), 2008)
This research aims at analyzing the spread information level of “Children Special Protection” (CSP) program to children-street community in Makassar and on how its information to influence their behavior like as to emerge consciousness for no goes down the street. This research aims also to analyze obstructions of the spread information of CSP program for children-street in Makassar. The method used in this research is descriptive-qualitative method by watching children-street in their living, their interaction, and tries to know their interpretation to surrounding world. The research informant uses snowball method and the key informant chosen by taking the intentional (purposive). Beside the observation activity, the collected data uses also deep-interview with informant and key informant, and analyses to spread information activities that executes by Dinas Sosial. The result of this research shows that the concept of the spread information of CSP in Makassar is not covering the substantive of field problem. The chosen communicator, arrange and message presentation, a chosen and media planning, and chosen and understand to people target by Dinas Sosial Pemkot Makassar is not yet executed well, adopted information process is inclined to the  perception only. Its information estimates to needless and the other influence factor is lower education level, which has children-street.